PENGELOLAAN INFAQ ZAKAT DAN SEDEKAH - Haikal, Fikri; Misbahuddin; Nur Taufiq Sanusi (Iqtishaduna: Jurnal Ilmiah Mahasiswa Hukum Ekonomi Syariah, 2024)
Abstrak Pokok masalah penelitian ini bagaimana pengelolalan zakat infaq dan sedekah. Dari pokok masalah tersebut maka dirumuskanlah sub masalah yaitu: Bagaimana proses pengelolaan zakat infaq dan sedekah dan bagaimana peran zakat infaq dan sedekah dalam perekonomian Indonesia. Penelitian ini bersifat kepustakaan (library research) yakni mengkaji beberapa jurnal buku dan beberapa pendapat ahli hukum atau ulama yang berkaitan dengan pengelolaan infaq zakat dan sedekah. Infaq merupakan pengeluaran sebagian harta atau pendapatan untuk kepentingan yang diperintahkan agama Islam. Zakat adalah harta yang wajib dikeluarkan oleh muzakki sesuai dengan ketentuan syariah dan diberikan kepada orang yang berhak menerimanya. Sedekah adalah pemberian secara suka rela harta atau bahan makanan untuk kebutuhan orang lain. Salah satu cara untuk meningkatkan perekonomian dan mengentaskan masalah kemiskinan adalah dengan memberdayakan ummat melalui infaq zakat dan sedekah. Infaq zakat dan edekah merupakan cara untuk mengurangi masalah perekonomian seperti kemiskinan. Infaq zakat dan sedekah mempunyai potensi besar jika digunakan untuk memberdayakan ummat. Dengan adanya infaq zakat dan sedekah menjadi salah satu instrumen ekonomi untuk pembukaan lapanngan pekerjaan yang baru dan mendorong tumbuhnya ekonomi rakyat. Pengelolaan infaq zakat dan sedekah dikelola oleh badan khusus yang ditunjuk negara sebagai pengelola infaq zakat dan sedekah. Infaq zakat dan sedekah dikelola oleh Badan Amil Zakat Nasional yang berdiri secara independen yang bertugas menghimpun dan menyalurkan zakat infaq dan sedekah pada tingkat nasional. Kata Kunci: Pengelolaan, Infaq, Zakat, Sedekah Abstract The main problem in this research is how to manage zakat and alms infaq. From this main problem, the following sub-problems were formulated: What is the process of managing zakat and alms infaq and what is the role of zakat and alms infaq in the Indonesian economy. This research is of a library research nature, namely examining several book journals and several opinions of legal experts and ulama relating to the management of zakat and alms infaq. Infaq is the expenditure of part of one's assets or income for purposes ordered by the Islamic religion. Zakat is property that must be released by muzakki in accordance with sharia provisions and given to people who are entitled to receive it. Alms is the voluntary giving of property or foodstuffs for the needs of others. One way to improve the economy and alleviate the problem of poverty is to empower the community through infaq zakat and alms. Zakat and alms donations are a way to reduce economic problems such as poverty. Zakat and alms donations have great potential if used to empower the community. With the existence of infaq, zakat and alms become an economic instrument for opening new job opportunities and encouraging the growth of the people's economy. The management of zakat and alms infaq is managed by a special agency appointed by the state as the manager of zakat and alms infaq. Zakat and alms infaq are managed by the National Zakat Amil Agency which is established independently and is tasked with collecting and distributing zakat infaq and alms at the national level. Keywords: Menjament, Infaq, Zakat, Alms